Population Estimation of Proboscis Monkeys in Mangroves at Kuching Wetland National Park, Sarawak - Aziz, Ahmad Fitri; Mergie Laman, Charlie Justin (Borneo Journal of Resource Science and Technology, 2018)
Boat survey on proboscis monkey (Nasalis larvatus) population in Kuching Wetland National Park (KWNP) was conducted to estimate the current population density and population size of this primate. The survey was conducted on September 2015 and January 2016 covering a cumulative distance of 128.91 km of mangrove riverbank. A cumulative total of 158 individuals comprising 19 groups, including one all-male group and three solitary males were recorded throughout the survey. The population density of proboscis monkeys in mangrove forest at KWNP was estimated at 1.63 individuals/km2 or 0.20 groups/km2. Based on the extrapolation of the estimated population density data, the population size of proboscis monkey in mangrove forest at KWNP was estimated to be 82 individuals. Last published report on the estimation of proboscis monkey population in Sarawak was more than 30 years ago. This study was conducted as a part of the efforts to assess the current population status of proboscis monkey in Sarawak. Keywords: Estimation, population density, population size, proboscis monkey